The Effect of Gamal Leaf Liquid Organic Fertilizer on the Growth of Arabica Coffee (Coffea Arabica L.) Seedlings in Polybags - Asgar; Ridwan; Rahmawati; Annadira (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
This research was carried out for 3 months, namely from March 2023 to June 2023, located at the BPDAS-HL Palu-Poso Permanent Nursery, this study used the Complete Randomized Design method consisting of 4 treatments, namely P0 = 0%, P1 = 20%, P2 = 30% and P3 = 30%. The four treatments were repeated seven times, bringing the total sample to 28 experimental units. The parameters observed are the increase in seedling height, stem diameter and number of leaves. The data analysis used is fingerprint analysis (F test) fingerprint analysis shows that the best treatment, it will be continued with further tests, namely the BNJ test level of 5%. The results showed that the concentration treatment of liquid organic fertilizer made from gamal leaves had a real influence on the increase in height, stem diameter and number of leaves in arabica coffee seedlings. The best treatment in this study was 40% concentration treatment (P3) with an average seedling height of 15.27 cm, an average seedling stem diameter of 3.17 mm and an average number of seedling leaves of 12.28 strands and the results of BNJ fingerprint analysis with an average height of 5.59 cm, number of leaves of 1.2 strands and stem diameter of 0.88 mm.